Profil Pengelolaan Kegiatan Ekstrakurikuler Tari Di SMP Negeri 12 Padang - Hasfira Benny Pratama; Ismaniar Ismaniar (Universitas Negeri Padang, 2023)
This research is motivated by the phenomenon of uniqueness. a different training method system because it works with studios, Padang 12 Public Middle School and extracurricular members who benefit financially. The purpose of this study was to find out how the management of dance extracurriculars at Padang 12 Public Middle School so that they can excel, and appear in many competitions, official events, and even the West Sumatra television station. This study uses a qualitative approach with descriptive methods. The data sources from this study are dance extracurricular coaches, vice principal for student affairs, curriculum assistant teachers, students who are members of dance extracurricular sales at SMP Negeri 12 Padang, and students who are not involved in dance extracurricular activities. Data collection techniques carried out in this study were observation, interviews, and documentation. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. While the data validity technique uses method triangulation, source triangulation, and theory triangulation. The results of this study indicate that (1) in dance extracurricular activities set goals in advance, create strategies so that activities are carried out well, create strategies so that students can excel, involve all residents in carrying out activities, determine activity budgets and determine activity schedules. (2) In dance extracurricular organizing activities, a management structure has been created even for members, recruiting members, providing the necessary infrastructure. (3) for dance extracurricular movement activities, they have carried out activities well, and provided motivation to dance extracurricular members (4) during dance extracurricular supervision activities, they have evaluated activities even though they are not yet formal and have also carried out problem analysis and ways to solve them (5) benefits What is gained by dance extracurricular members is to increase their self-confidence, to be able to develop their potential, and to gain financial benefits.Keywords: Pengelolaan Kegiatan Ekstrakurikuler Tari